Relationship between empathy and burnout as well as potential affecting and mediating factors from the perspective of clinical nurses: a systematic review - Hongyan Zhou (BMC Nursing)
Abstract Background Burnout is prevalent in healthcare professionals, especially among nurses. This review aims to examine the correlation between empathy and burnout as well as the variables that influence and mediate them. Methods This review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline, to present a systematic evaluation of literature. A literature search of four electronic databases including CINAHL (EBSCO), EMBASE, PubMed, and Google Scholar was conducted from 2014 to 2024. A total of 1081 articles were identified in the initial search. After screening the title, abstract, and context of these articles, 16 eligible articles were finally included in this review. Results This review identified a number of factors related to empathy and burnout levels. The included studies showed consistent results that empathy and burnout were generally negatively related. When considering the different components of empathy or burnout independently, as well as the mediating factors involved, relations between empathy and burnout may alter. Conclusions This study provided an excellent summary of some important research on the mediating and affecting factors associated with burnout and empathy. These results can facilitate further development of interventions and policies to better manage and prevent burnout in nurses.